Impact of Reclamation on Capture Fisheries in Jakarta Bay - Nono Sampono; Ari Purbayanto; John Haluan; Ahmad Fauzi; Budy Wiryawan (JURNAL PERIKANAN DAN KELAUTAN, 2012)
Jakarta is the capital of the state whose condition is very dense; to meet the requirement of land for the development and expansion of Jakarta, the reclamation of Jakarta Bay was planned. In addition to overcome the limitations of the land, reclamation activities will also be able to play a very important role in the rearrangement and can give a distinctive character to the area Ancol Beach. One of the activities affected due to the reclamation of Jakarta Bay is a fisheries activity. Fishermen in the Bay of Jakarta actually have shown opposition to reclamation, so the control of ongoing projects and activities related to dredging is necessary to ensure that the impacts are very minimal impact on fisheries and aquaculture activities. It was required a study of the impact of reclamation on fisheries activities and fishermen adaptation. The objectives of this study are (1) to understand the knowledge and acceptance of the fishermen to the reclamation activity, (2) to understand the fishing community's perception of the impact of reclamation and (3) to understand the patterns of adaptation of the fishing communities due to the reclamation. Desktop study and interview were conducted to collect the data. Calculation of composition and GIS analysis were conducted to analyze the data. The level of knowledge of fishermen in Cilincing, Muara Angke and Muara Baru on reclamation activities showed a low level of knowledge. Sedimentation during the reclamation process is a major concern to the fisheries. Some fishermen said the reclamation had no impact on the fishing areas. Fishermen will keep trying to catch fish even have to move their fishing areas or have to move their village.Keyword: reclamation, Jakarta Bay, fisheries, fisherman